Does an expanding low-pay sector decrease structural unemployment? Evidence from Germany - Marcel Garz; Artur Tarassow (Hamburg University, Department Economics and Politics, 2011)
Low-pay work has been increasing in prevalence in many industrial countries. Following standard wage/price-setting theory, this increase should reduce structural unemployment, because labour market flexibility increases and labour costs decrease. However, a Keynesian perspective challenges this claim, if the associated increase in investment demand does not sufficiently compensate for the negative effects on consumption. This research empirically investigates the theoretically uncertain impact of the relationship between the extensiveness of the low-pay sector and structural unemployment. Data from Germany, where the expansion of the low-pay sector has been declared the goal of the labour market policy, during the period from 1991 to 2008, indicate a positive impact of the growing low-wage sector on structural unemployment. Moreover, some indications suggest an opposite direction of causality, such that changes in the level of structural unemployment affect the share of low-wage earners. This effect is asymmetrical with respect to positive and negative changes, which seems to reflect downward wage rigidity, as caused by labour market institutions.
Keywords: C32; E24; J31; 330; NAIRU; low-wage; asymmetric error correction; cointegration; VECM